Undetected cancer in clinical prostate biopsies ... : Undetected cancer in clinical prostate biopsies ... - Chelebian, Eduard; Wählby, Carolina; Bergh, Anders (Uppsala University, 2024)
This dataset comprises digitized benign prostate hematoxilyn and eosin (H&E) biopsies from men with raised prostate-specific antigen (PSA) values. The biopsies were systematically taken from different locations in the prostate and were not guided by magnetic resonance imaging (MRI). The dataset includes paired samples from patients with comparable age and PSA levels, all initially diagnosed as benign but with different outcomes upon subsequent follow-ups and re-biopsies. While some patients remained cancer-free during eight years of follow-up, others were diagnosed with prostate cancer within the subsequent 30 months of follow-up. The final processed dataset includes 213 patients from northern Sweden, resulting in a total of 587 H&E prostate needle biopsies. Among these, 125 control patients with 333 biopsies exhibited no cancer development in eight years following the initial diagnosis. Conversely, 88 case patients with 254 biopsies were diagnosed with prostate cancer of various ISUP grades within ... : Datasetet består av digitiserade godartade prostata H&E-biopsier från män med förhöjda PSA-värden. För mer information, se beskrivning på engelska: This dataset comprises digitized benign prostate hematoxilyn and eosin (H&E) biopsies from men with raised prostate-specific antigen (PSA) values. The biopsies were systematically taken from different locations in the prostate and were not guided by magnetic resonance imaging (MRI). The dataset includes paired samples from patients with comparable age and PSA levels, all initially diagnosed as benign but with different outcomes upon subsequent follow-ups and re-biopsies. While some patients remained cancer-free during eight years of follow-up, others were diagnosed with prostate cancer within the subsequent 30 months of follow-up. The final processed dataset includes 213 patients from northern Sweden, resulting in a total of 587 H&E prostate needle biopsies. Among these, 125 control patients with 333 biopsies exhibited no cancer development in eight ...